FENOMENA KENCAN ONLINE DALAM DATING APPS - Nova Asharina Wicaksono; Totok Wahyu Abadi (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
Bumble and Tinder are dating apps for those who struggle with online dating-based romance. They allow you to share personal data through a smartphone application, without the need for direct conversation. This study aims to explain the phenomenon of online dating with Dating Apps and the meaning of using Dating Apps Bumble and Tinder from the perspective of Computer-Mediated Communication and Coordinated Management of Meaning. The basic concepts used in this research are the theory of Computer-Mediated Communication from Joseph Walther and the Coordinated Management of Meaning from W. B Pearce and V Cronin. In this qualitative research, informants are determined using purposive sampling and participant observation. The data collection techniques used in this study were observations and interviews with six women and three men who were active users of Bumble and Tinder. The results of this research show a pattern of gender relations in the use of the Bumble or Tinder applications. Bumble gives women more control over relationship development or termination compared to Tinder. The shared meaning of